Kemunculan Ancaman Siber Teknologi 5G dan Implikasinya terhadap Ketahanan Siber di Jakarta - Vincha, Chiara; Satrio, Jati (Jurnal Ketahanan Nasional, 2024)
ABSTRACT             One of the main trends in technological development is the emergence of the 5G technology internet network. This technology offers more powerful capabilities. Because of this, the Indonesian government is also committed to implementing the technology on a massive scale. The government, through the National Cyber and Crypto Agency (BSSN), has realized that 5G technology not only creates opportunities for national development but also presents new cyber threats to national cyber security.This research aims to analyse the implications of the emergence of 5G technology for Indonesia's cyber resilience, where the author will use the dual-use security dilemma concept. This research uses exploratory qualitative method with interview and literature study as its data collection techniques. The interviews were held with the National Cyber and Crypto Agency (BSSN) employees from the Directorate of Cyber and Crypto Security Strategy and cyber security observers. The literature study method used internet sources, news, books, journals, articles, previous studies, and other scientific papers related to the topic. The data is presented using descriptive analysis method.From the results, the author found that the dual-use security dilemma of 5G technology has encouraged the Indonesian government to develop a National Cyber Security Strategy that can maintain cyber resilience with the emergence of new cyber threats from this technology